Exploring the courage of accounting students in disclosing fraud - Oktaria Nysa Wardani; Indrawati Yuhertiana (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to explore the courage of accounting students to become a whistleb-lower. The paradigm of this study is qualitative interpretive. The research site is at University of Pembangunan Nasional â€œVeteranâ€ Jawa Timur, with 4 accounting students selected as the informants. The results show that the accounting students have a low level of courage. In addition to individualâ€™s intention and courage, there is no support from the environment, or the so-called negative subjective norms. This spontaneously causes a negative perception on whistle-blowing, thus reducing people's motivation to take action. The informants consider that there are still more important things to do than to perform whistle blowing. National defense philosophy, nationalism and religiosity need to be implemented in the learning process. It requires the support of the entire academic community related to the values of honesty and ethics, especially from the role models of lecturers and college leaders.